2020
DOI: 10.4103/joc.joc_57_19
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between thyroid imaging reporting and data system and bethesda system of reporting of thyroid cytopathology of thyroid nodule: A single center experience

Abstract: Background: The incidence of thyroid cancer has been increasing worldwide. Thyroid imaging reporting and data system (TIRADS) has been proposed for risk stratification of thyroid nodules to improve categorical management. Fine needle aspiration cytology based on Bethesda system for reporting of thyroid cytopathology (BSRTC) plays a fundamental role in the evaluation of thyroid nodule microscopically. Both the systems, the TIRADS and the latest revised BSRTC 2017, are widely recommended and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…This can be attributed to the lack of TIRADS scoring in routine practice and the loss to follow-up of patients. It was mostly comparable with the study by Biswas et al9 , with the highest concordance for TIRADS-2, with ROM values of 10.3% and 10.8% respectively, and for TIRADS-5, with ROM values of 100% in both studies. Another study by Moifo et al14 found ROM values of 57.9% and 100% for TIRADS scores 4 and 5…”
supporting
confidence: 90%
See 3 more Smart Citations
“…This can be attributed to the lack of TIRADS scoring in routine practice and the loss to follow-up of patients. It was mostly comparable with the study by Biswas et al9 , with the highest concordance for TIRADS-2, with ROM values of 10.3% and 10.8% respectively, and for TIRADS-5, with ROM values of 100% in both studies. Another study by Moifo et al14 found ROM values of 57.9% and 100% for TIRADS scores 4 and 5…”
supporting
confidence: 90%
“…The ROM in the present study for each TBSRTC category was much higher when compared to the standard TBSRTC system, especially for categories II to V. A 2020 study by Biswas et al 9 with a sample size of 69 cases found a ROM of 5.13% for category II, which was comparable to the TBSRTC system ROM of 0%‐3%; in the present study, a ROM of 11.3% was found for this category. The ROM for category III was 20% both in this study and that of Biswas et al The largest discrepancy was found in category IV, with a ROM of 61.5% in this study, 28.5% by Biswas et al, and 15%‐30% suggested by TBSRTC.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The investigators found that results for nodules categorized as TBSRTC II, V, and VI are comparable to previous studies. [9][10][11] Findings for nodules categorized as TBSRTC I and III were not previously elucidated.…”
Section: Discussionmentioning
confidence: 99%